Using a paleosurface to constrain Low‐Temperature Thermochronological Data: Tectonic evolution of the Cuevas Range, Central Andes - Zapata, S. (2019)
Dispersion of low-temperature thermochronologic data from nine samples collected on a deformed paleosurface preserved on the Cuevas range (Central Andes) can be exploited to unravel complex thermal histories. The nine samples yielded data that have both intersample and intrasample dispersions; the data set includes apatite fission-track ages (180–110 Ma), mean track lengths (11–13 μm), apatite helium (10–250 Ma), and zircon helium ages (180–348 Ma). We ran inverse thermal history models for each sample that reveal spatial variations of the Miocene reheating along the paleosurface. Next, we ran a multiple-sample joint model to infer a common form for thermal history for all samples. Our results suggest that initial exhumation during the Famatinian orogeny was followed by a residence between ~2.5 and 7.0 km depth during the Paleozoic and the Triassic. The onset of Mesozoic rifting was responsible for an increase of the geothermal gradient and extensive horst exhumation, which brought the basement of the Cuevas range close to the surface (~1–2 km) in the Late Jurassic. Between the Late Cretaceous and the Paleocene, the combination of low relief, a humid climate, and low erosion rates (0.006–0.030 km/Ma) facilitated the development of the Cuevas paleosurface. During the Miocene, this paleosurface experienced differential reheating with a high geothermal gradient (>25 °C/km) due to the sedimentary cover and local magmatic heat sources. During the Andean orogeny, in the Pliocene, the Cuevas paleosurface was deformed, exhumed, and uplifted.